Levantamiento geológico-estructural de la vía antigua Loja-Cuenca de la abscisa 6+000 hasta 10+500 del Barrio Sevilla de Oro del Cantón y Provincia de Loja - Mendoza Calva, Yazmín Tatiana (2024)
The structural geological survey at a scale of 1:5000, carried out the old Loja - Cuenca road from abscissa 6+000 to 10+500, belongs to Barrio Sevilla de Oro, Canton and Province Loja, has an extension of 4.5 kilometres and an area of 1.76 square kilometres. The geological structural characterization was carried out through the contact mapping method, it allowed characterize two lithological units. The Agoyan unit is mainly composed of shales, schists, phyllites and corneanas, just as the Tres Lagunas unit is organised by granitoids (granodiorite), colluvial deposits composed of angular blocks of volcanic and metamorphic rocks; alluvial deposits composed of poorly consolidated material, with pebbles and blocks of generally metamorphic and volcanic rocks. Structurally, photo-interpretation has identified one normal-type fault and three zones of microfaults, two diaclast zones and three contacts. This will help in the subsequent structural geological map. Having all the information of the field work, performed to make the structural geological map scale 1:500, ArcGis 10.5 software was used to help us reflect the geological and structural conditions of the study area. Keywords: Structural geology, lithological unit, contact mapping, geological survey.